Discovery of two novel β‐glucosidases from an Amazon soil metagenomic library. Issue 2 (16th December 2013) - Bergmann, Jessica C.; Costa, Ohana Yonara A.; Gladden, John M.; Singer, Steven; Heins, Richard; D'haeseleer, Patrik; Simmons, Blake A.; Quirino, Betania F.
Abstract An Amazon soil microbial community metagenomic fosmid library was functionally screened for β‐glucosidase activity. Contig analysis of positive clones revealed the presence of two ORFs encoding novel β‐glucosidases, AmBGL17 and AmBGL18, from the GH3 and GH1 families, respectively. Both AmBGL17 and AmBGL18 were functionally identified as β‐glucosidases. The enzymatic activity of AmBGL17 was further characterized. AmBGL17 was tested with different substrates and showed highest activity on pNPβG substrate with an optimum temperature of 45 °C and an optimum pH of 6. AmBGL17 showed a Vmax of 116 mM s−1 and Km of 0.30 ± 0.017 mM. This is the first report of β‐glucosidases from an Amazon soil microbial community using a metagenomic approach.